2021
DOI: 10.1002/mp.14685
|View full text |Cite
|
Sign up to set email alerts
|

Application of radiochromic gel dosimetry to commissioning of a megavoltage research linear accelerator for small‐field animal irradiation studies

Abstract: Purpose To develop and implement an efficient and accurate commissioning procedure for small‐field static beam animal irradiation studies on an MV research linear accelerator (Linatron‐M9) using radiochromic gel dosimetry. Materials The research linear accelerator (Linatron‐M9) is a 9 MV linac with a static fixed collimator opening of 5.08 cm diameter. Lead collimators were manually placed to create smaller fields of 2 × 2 cm2, 1 × 1 cm2, and 0.5 × 0.5 cm2. Relative dosimetry measurements were performed, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
(69 reference statements)
1
3
0
Order By: Relevance
“…Whereas the depth-dose curves were well-fit with the Monte-Carlo calculation below the depth of maximum dose ( d max ), there was a noticeable over-response in the dose build-up region close to the top of the gel, which may be attributed to the effect of the dissolved oxygen near the surface of the gel. A similar effect was previously reported in fresh samples of ClearView [ 24 ] but was absent in well-sealed and aged gels [ 16 , 19 ]. To avoid uncertain dose sensitivity near the top surface of the gel, the jars used in the follow-up tests were sealed with heat-adhesive aluminum foil and aged for a week before use.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Whereas the depth-dose curves were well-fit with the Monte-Carlo calculation below the depth of maximum dose ( d max ), there was a noticeable over-response in the dose build-up region close to the top of the gel, which may be attributed to the effect of the dissolved oxygen near the surface of the gel. A similar effect was previously reported in fresh samples of ClearView [ 24 ] but was absent in well-sealed and aged gels [ 16 , 19 ]. To avoid uncertain dose sensitivity near the top surface of the gel, the jars used in the follow-up tests were sealed with heat-adhesive aluminum foil and aged for a week before use.…”
Section: Resultssupporting
confidence: 87%
“…However, as initially developed, tetrazolium salt gel dosimeters tend to have lower sensitivity compared to other radiochromic 3D dosimeters [ 3 ], as well as an appreciable dose rate effect at dose rates below approximately 600 cGy/min [ 12 ]. Developed in our laboratory, a new gel dosimeter has been commercialized under the name ClearView by Modus Medical Devices Inc. (Modus QA), (London, ON, Canada) and primarily used for geometric registration of small-beam irradiation [ 14 , 15 , 16 ] and end-to-end dosimetric evaluation of single isocenter multi-target treatment and prostate plan validation [ 17 ]. The initial results indicated that the relatively low sensitivity to dose and the dose rate effect of the sensitivity may cause misregistration of the delivered dose plan.…”
Section: Introductionmentioning
confidence: 99%
“…ClearView (ModusQA) is a novel single use radiochromic gel dosimeter designed for use with optical CT for relative dosimetry measurements with several published accounts of use 1–6 . When exposed to ionizing MV radiation, ClearView gel changes color from optically clear to purple through the reduction of a water‐soluble tetrazolium salt into an insoluble formazan dye.…”
Section: Introductionmentioning
confidence: 99%
“…INTRODUCTION ClearView (ModusQA) is a novel single use radiochromic gel dosimeter designed for use with optical CT for relative dosimetry measurements with several published accounts of use. [1][2][3][4][5][6] When exposed to ionizing MV radiation, ClearView gel changes color from optically clear to purple through the reduction of a water-soluble tetrazolium salt into an insoluble formazan dye. Independent studies 1,2,4 and the User's Guide 7 have reported the change in optical attenuation to be linear with dose between 0 and 80 Gy, with negligible signal diffusion and change with time (aging of irradiated gel ∼3 × 10 −4 cm −1 /day), low optical scattering component, and near tissue equivalence (electron density 1.015 ± 0.3% relative to water).…”
mentioning
confidence: 99%